2016
DOI: 10.3389/fpls.2016.01329
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Eco-Physiological Responses to Drought Mirrors the Distinct Distribution of Chamerion angustifolium Cytotypes in the Himalaya–Hengduan Mountains Region

Abstract: Polyploid species generally occupy harsher habitats (characterized by cold, drought and/or high altitude) than diploids, but the converse was observed for Chamerion angustifolium, in which diploid plants generally inhabit higher altitudes than their polyploid derivatives. Plants at high altitudes may experience cold-induced water stress, and we therefore examined the physiological responses of diploid and hexaploid C. angustifolium to water stress to better understand the ecological differentiation of plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 104 publications
1
24
0
1
Order By: Relevance
“…SAMPLE PREPARATION AND FLOW CYTOMETRY STUDY. Investigation of GS was performed in a flow cytometer as described previously (Guo et al, 2016). In brief, young leaves were collected from each turnip seedling and kept on ice until processing, which occurred within one h of sample collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SAMPLE PREPARATION AND FLOW CYTOMETRY STUDY. Investigation of GS was performed in a flow cytometer as described previously (Guo et al, 2016). In brief, young leaves were collected from each turnip seedling and kept on ice until processing, which occurred within one h of sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…For example, researchers who studied large-scale cytotype distribution (McAllister et al, 2015) hypothesized that higher GS plants adapt better in high altitudes than lower GS plants. However, the results of some studies are inconsistent with this hypothesis (Guo et al, 2016). For instance, Bennett et al (1982) indicated that lower GS plants have increased tolerance in highlands.…”
mentioning
confidence: 97%
“…In turn, triploids (n=27) appear in mixed-ploidy populations of border areas [40]. The hexaploid cytotype was reported only in central Japan and the Yunnan province of China [36,41].…”
Section: Distribution and Habitatsmentioning
confidence: 99%
“…short-term, as well as long-term growth and fitness related plant traits and their mutual interplay should thus be considered to understand the specific mechanisms behind the response. Most of the existing studies exploring differences between cytotypes in response to stress are, however, focused on either physiology and morphology of plants [ 20 , 35 40 ] or fitness traits [ 22 , 41 , 42 ]. Only a single study focused on both physiological and fitness traits in the same experiments [ 43 ].…”
Section: Introductionmentioning
confidence: 99%